Task-Specific Engagement of Object-Based and Space-Based Attention with Spatiotemporally Defined Objects - Zheng, Qingzi (Atten Percept Psychophys, 2021)
We used a form of ambiguous apparent motion known as Ternus motion to isolate the effects of object-based and space-based attention, and to explore functional differences between them. Two frames of horizontally aligned disks that were shifted by one position between frames, were temporally separated by either a short or a long inter-stimulus interval (ISI). Short ISI displays were perceived as element motion where one disk appeared to jump across the other two. Long-ISI displays were perceived as group motion where all three disks appeared to move together. Because element and group motion imply mutually exclusive object structures, adding stimuli (e.g., a small gap) to one disk in each frame created conditions of orthogonal object and location status (same or different), depending on ISI. We used two tasks with different functional demands, an identification task (Experiments 1 and 3a) in which observers responded to a single attribute of the final stimulus, and a comparison task (Experiments 2 and 3b) in which observers compared two attributes across two stimuli. Reliable object-specific effects occurred only with the comparison task, whereas location-specific effects occurred with both tasks. These results confirm that attention can be directed to objects separately from spatial locations and vice versa, and moreover, that object-based and space-based attention are engaged differently depending on the processing demands of the task.